2009
DOI: 10.1142/s0219199709003648
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Analysis of Periodically-Perforated Nonlinear Media at the Critical Exponent

Abstract: We give a Γ-convergence result for vector-valued nonlinear energies defined on periodically perforated domains. We consider integrands with n-growth where n is the space dimension, showing that there exists a critical scale for the perforations such that the Γ-limit is non-trivial. We prove that the limit extra-term is given by a formula of homogenization type, which simplifies in the case of n-homogeneous energy densities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…This can be done explicitly if K is a ball, and gives (6) as a result. Note that in this case the radius of K does not affect the result; we can therefore extend the result to arbitrary K with nonempty interior by comparison with the case of balls containing K or contained in K, respectively, and conclude that the form of the limit is indeed independent of the shape of K. Further technical arguments are needed when f is not positively homogeneous; a detailed proof can be found in [9].…”
Section: Asymptotic Behaviour At the Critical Scalingmentioning
confidence: 67%
See 3 more Smart Citations
“…This can be done explicitly if K is a ball, and gives (6) as a result. Note that in this case the radius of K does not affect the result; we can therefore extend the result to arbitrary K with nonempty interior by comparison with the case of balls containing K or contained in K, respectively, and conclude that the form of the limit is indeed independent of the shape of K. Further technical arguments are needed when f is not positively homogeneous; a detailed proof can be found in [9].…”
Section: Asymptotic Behaviour At the Critical Scalingmentioning
confidence: 67%
“…Our arguments show that the exponential regime derives from the scaling invariance of the problems in (9), which eliminates the pre-factor ε n−p , and from the logarithmic behaviour of minimizers. We have shown that the usual 'capacitary' formula for the limit integrand ϕ in the case p < n is substituted by an interesting 'homogenization' formula.…”
Section: Remarkmentioning
confidence: 82%
See 2 more Smart Citations
“…To obtain case (2), we first treat the case of K a single hyperplane and ϕ(x, z) = c 1 + c 2 z 2 . This can be obtained following arguments similar to those by Ansini [4] to approximate the energy density c(u + − u − ) 2 on a surface (Neumann sieve) coupled with the description of the effect of pinning sites at the critical scaling by Sigalotti [26,27]. Note that the computation of the interfacial energy gives the same constant as in the continuous case for n = 2, while it highlights a more complex behavior for n ≥ 3, where a fraction of the total contribution is actually given by the strong springs at the interface, which sums up to the contribution distributed away from the interface and summarized in a capacitary formula.…”
mentioning
confidence: 99%